The Effect of Service Quality and Facilities on Customer Satisfaction of Waste Management Service Users at BUMDesa (Village-Owned Enterprises) Sima Sari Dana Kesiman Petilan - Gusti Nyoman Tri Purnami Wati; Mahayanti Fitriandari (Social and Economic Bulletin, 2024)
Customer satisfaction is one of the many things that can contribute to achieving the company's vision. Success in achieving the company's vision and mission is determined by several factors, namely customer satisfaction, including service quality and facilities. Likewise in the BUMDesa (Badan Usaha Milik Desa) Sima Sari Dana Kesiman Petilan, the quality of service and facilities is factors that can affect customer satisfaction. The purpose of this study to determine the partial and simultaneous effect of service and facility quality variables on customer satisfaction using waste management services in BUMDesa (Badan Usaha Milik Desa) Sima Sari Dana Kesiman Petilan. The sample was carried out using purposive sampling, as many as 79 respondents. Data collection methods used are observation, interviews, literature study and questionnaires. The data analysis technique used is quantitative analysis which consists of classical assumption test, multiple linear regression analysis, analysis of determination, statistical analysis of F-test and statistical analysis of T-test. The results showed that there was a positive and significant influence simultaneously and partially between the quality of service and facilities on customer satisfaction of waste management service in the BUMDesa (Badan Usaha Milik Desa) Sima Sari Dana Kesiman Petilan.